The Influence of Organizational Culture on Employee Performance at Bappeda and Statistics of Bone Regency - Suparman Mekka; Wahyuddin Hamid; Henni Zainal; Aksa Aksa (Pinisi Business Administration Review, 2020)
Fun work culture create a positive employee attitude and gave impetus to work more diligently and more good.Aims this study was to determine the influence of organizational culture on organizational commitment in Bappeda and Statistics of Bone. Research uses explanatory research with a quantitative approach (positivism). Explanatory research explains the causal relationship between variables that influence the hypothesis. The results show that organizational culture has a significant positive effect on employee performance. This organizational culture can be seen from employee empowerment, team orientation, clarity of vision, direction and organizational goals. The stronger the organizational culture, the higher the performance.